Rhizoremediation of Petrol Engine Oil Using Biosurfactants Producing Microbial Consortium in Mustard Crop - Kumar, Govind; Kumar, Rajesh; Sharma, Anita (International Journal of Applied Sciences and Biotechnology, 2015)
Contamination of soil / water resources by petroleum products poses severe threats to underground water and soil quality. In the present study biosurfactant producing bacterial cultures were used to degrade petrol engine oil under in situ conditions in the plant rhizosphere system. Two bacterial isolates used in this study were recovered from Haldia oil refinery sites and identified as Pseudomonas aeruginosa (JX100389) and P. moraviensis (JX149542). Application of consortium C2, (Pseudomonas aeruginosa and P. moraviensis) degraded 79.02 % petrol engine oil @ 2% in the soil planted with mustard (Brassica juncea var. Kranti) crop after 120 days. GC-MS of biodegraded fuel showed the presence of new product like hexadecanoic acid 2, oxo-methyl ester. Int J Appl Sci Biotechnol, Vol 3(2): 261-266 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12475